(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
The school of Uppsala proposes a model that considers the gradual increase in the level of internationalization, which would by obtaining knowledge about new markets and the commitment of resources. Changes in the business environment and theoretical readings led to the recognition of the influence of business networks on the processes of learning and obtaining knowledge of the companies that internationalize. This study aims to revisit the Uppsala model from the perspective of resource-based (RBV). Through literature review, we analyze the commonalities between the two approaches and their complementarities. Thus, we intend to discuss the role of resources and their importance to the generation of knowledge and learning of the companies during the internationalization process.